Noah and the devil : a legend of Noah's Ark from Romania - Philip, Neil (Clarion Books, 2001)
A retelling of the story of Noah's ark, embellished with elements from Romanian folklore, including how the devil sneaked aboard, the reason Noah threw a cat overboard, and the role of a snake in saving the ark.